Knowledge and practices of food in pregnant women attended in a hospital in lima, 2017: Conocimientos y prácticas de alimentación en gestantes atendidas en un hospital de lima, 2017 - Francia-Ramos, Cinthia (2018)
Objective: To determine the association between knowledge and feeding practices in pregnant women attended in a Hospital in Lima, 2017.  Methods: The study design is observational, quantitative, analytical and transversal. A sample of 279 pregnant women was selected who attended in Hospital Vitarte during the month of September 2017, evaluated by the surveys that measured the study parameters. Later, the data were analyzed by the statistical SPSS version 22. The frequencies of the main variables were obtained, for the degree of association the basis of the calculation of the probabilities and the 95% confidence intervals were applied. In addition, the significant chi square was analyzed with p <0.05. Results: It was demonstrated that knowledge about feeding and feeding practices in pregnant women had no significant participation (p = 0.51, OR = 1.4, 95% CI: 0.63-2.45). In addition, the knowledge of acceptable weight during pregnancy is associated with the consumption of junk food in pregnant women (p=0.023, OR=1.73, IC95%:1.08-2.79). Likewise, feeding practices are associated to the parity in pregnant women (p = 0.001, OR = 3.04, IC95%: 1.56-5.9). Conclusion: Only 25.8% of pregnant women have knowledge about feeding during pregnancy and 18.3% have adequate food practices. No association was found between knowledge and feeding practices in pregnant women and parity increases the likelihood of having adequate feeding practices. Key words: Food knowledge; Food practices; Pregnant. (source: MeSH NLM)